If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -3) = 2(7 + -1X) Reorder the terms: 4(-3 + x) = 2(7 + -1X) (-3 * 4 + x * 4) = 2(7 + -1X) (-12 + 4x) = 2(7 + -1X) -12 + 4x = (7 * 2 + -1X * 2) -12 + 4x = (14 + -2X) Solving -12 + 4x = 14 + -2X Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4x = 14 + 12 + -2X Combine like terms: -12 + 12 = 0 0 + 4x = 14 + 12 + -2X 4x = 14 + 12 + -2X Combine like terms: 14 + 12 = 26 4x = 26 + -2X Divide each side by '4'. x = 6.5 + -0.5X Simplifying x = 6.5 + -0.5X
| ln(x)=-7/12 | | 7(r-87)=35 | | -5(3x-11)=2(x-5)-37 | | 1/2x(x-35)=46 | | 2=f | | 3x+6y=12+3y | | 11.50-4-3.50= | | 11d=583 | | 2p+4p-p-3p+1=13 | | 11.50-4.00-3.50= | | q-308=588 | | 5x=5y+35 | | 2b-5-7=-14 | | 4*3-x=24 | | 0.3=p | | h/17=18 | | 4c-2c-c-c+2c=14 | | -15-7x=-8+10 | | 12x-5=60 | | 21+23f=28+16f | | 10x+15=60 | | 3.24-k=9.48 | | 4u+2=-6 | | 4(3m-2)-3(m+4)= | | 17r-15r-2r+4r+1=13 | | 9=z+10 | | (3-y)i=6i | | 3/5x3x3 | | 47+51=b | | 5k^2-8k+12=0 | | 14m-5m=18 | | Y=-5*14+4 |